2023
DOI: 10.1039/d2sc06984a
|View full text |Cite
|
Sign up to set email alerts
|

Excited state energy landscape of phosphorescent group 14 complexes

Abstract: Great progress has been achieved on phosphorescent or photoactive complexes of the Earth-abundant transition metals, while examples for phosphorescent heavy main group element complexes are rare, in particular for group...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…Heinze and co-workers reported the synthesis of tri-coordinate stannylene Sn47 via the transamination of H 2 bpep with the Sn(N(TMS) 2 ) 2 in the presence of DCM in 74% yield (Scheme 90). 117…”
Section: Overview Of the Synthesis Of Heavier Low-valent Compounds Of...mentioning
confidence: 99%
See 2 more Smart Citations
“…Heinze and co-workers reported the synthesis of tri-coordinate stannylene Sn47 via the transamination of H 2 bpep with the Sn(N(TMS) 2 ) 2 in the presence of DCM in 74% yield (Scheme 90). 117…”
Section: Overview Of the Synthesis Of Heavier Low-valent Compounds Of...mentioning
confidence: 99%
“…DFT calculation provided activation barriers of 0.29 eV and 0.23 for 3 ILCT/ 3 LMCT pyr and 3 ILCT/ 3 LMCT py (optimized transition states of compound Sn47 ), respectively. 117…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…53SnOTf was obtained as an air‐ and moisture‐sensitive orange solid. By using the unique tridentate ligand, the phosphorescence property from low‐valent tin ( 54Sn ) and lead ( 54Pb ) complexes were detected [128] . It was revealed that the tin complex ( 54Sn ) showed green intraligand charge transfer (ILCT) phosphorescence both in solution and in the solid state, meanwhile the lead complex ( 54Pb ) only showed very weak red phosphorescence from a strongly distorted ligand‐to‐metal charge transfer (LMCT) state at low temperatures in the solid state.…”
Section: Introductionmentioning
confidence: 99%